Probiotics or synbiotics addition to sows’ diets alters colonic microbiome composition and metabolome profiles of offspring pigs - Zhu, Qian; Song, Mingtong; Azad, Md. Abul Kalam; Cheng, Yating; Liu, Yating; Liu, Yang; Blachier, François; Yin, Yulong; Kong, Xiangfeng (Frontiers in Microbiology, 2022)
The present study evaluated the effects of probiotics or synbiotics addition to sows’ diets on colonic microbiota and their metabolites in offspring using 16S rRNA gene sequencing and metabolome strategy. A total of 64 pregnant Bama mini-pigs were randomly divided into control, antibiotic, probiotics, and synbiotics groups and fed the corresponding experimental diets during pregnancy and lactation. After weaning, two piglets per litter and eight piglets per group were selected and fed a basal diet. The most predominant phyla identified in colonic contents were Firmicutes and Bacteroidetes, regardless of the day of age. The abundances of Actinobacteria at 65 days of age and Tenericutes and Firmicutes at 95 days of age were higher in the probiotics group than the other three groups, as well as Spirochaetes and Proteobacteria at 95 days of age in the antibiotic group. Metabolomic analysis showed that colonic metabolites were different between each group, regardless of the day of age. Furthermore, both PICRUSt2 and enrichment analysis of metabolic pathways showed that maternal probiotics and synbiotics addition affected carbohydrate metabolism, amino acid metabolism, and metabolism of cofactors and vitamins in the colonic microbiota. Compared with the control group, the colonic concentration of indole decreased and skatole increased in the probiotics group, whereas the indole increased and skatole decreased in the synbiotics group. Maternal probiotics addition increased the colonic concentrations of acetate and butyrate at 65 and 125 days of age, whereas probiotics and synbiotics addition decreased short-chain fatty acids concentrations at 95 days of age. In addition, the colonic concentrations of putrescine, spermine, spermidine, and tryptamine increased in the antibiotic, probiotics, and synbiotics groups compared with the control group. The correlation analysis showed that there were positive correlations between acetate, propionate, and butyrate with Gemmiger, Roseburia, and Faecalibacterium; between putrescine, spermidine, and spermidine with Gemmiger, Blautia, and Faecalibacterium; and between (R)-3-hydroxybutyric acid with Faecalibacterium, Blautia, Clostridium, and Streptococcus. Collectively, these findings suggest that probiotics and synbiotics addition to sows’ diets exerts effects on offspring pigs by altering gut microbiota composition and their metabolites. The potential beneficial effect for gut health is discussed.